Antimicrobial starch-citrate hydrogel for potential applications as drug delivery carriers - Chin, Suk Fun; Ain Nadirah, Romainor; Pang, Suh Cem; Samuel, Lihan (Elsevier B.V., 2019)
Antimicrobial starch-citrate hydrogels were prepared by physical crosslinking of starch citrate, Poly(vinyl alcohol (PVA) and Polyethylene glycol (PEG) via the freeze–thaw technique. This starch-citrate hydrogel exhibited excellent antimicrobial activity against various bacteria strains such as Escherichia coli (gram negative), Staphylococcus pyogenes (gram negative), Salmonella thypimurium (gram positive) and Streptococcus aureus (gram positive). Most notably it showed antimicrobial activity against the multiple antibiotic resistant (M.A.R) superbugs (Klebsiella pneumoniae). Penicillin G loaded starch-citrate hydrogel was observed to exhibit a sustain release profile over 7 days. Penicillin G loaded starch-citrate hydrogel also exhibited synergistic antimicrobial activities against Salmonella thypimurium, Escherichia coli (E-coli) (O15:H7) and E-coli control (ATC 2925). The potential application of starch-citrate hydrogel as both antimicrobial agent and drug delivery carriers is therefore envisaged.